The Effects of Intellectual Capital Accumulation of Taiwan-Listed Electronics Companies on Financial Performance: Meta Analysis - Chen , Ching-Yaw; Hung, Feng-Chu; Lee, Yu-Je (Asian Journal of Empirical Research, 2014)
The primary purpose of this study is to understand the effects of the intellectual capital accumulation on the financial performance in Taiwan-listed Electronics Companies, and data in this study are collected based on previous studies done by domestic and international scholars using Meta Analysis to analyze the collected data. A conclusion has been made by this study, that the “intellectual capital accumulation” of Taiwan-listed Electronics Companies indeed makes a significantly positive effect on the “financial performance”.